2020
DOI: 10.7150/jca.47902
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of long non-coding RNA DUXAP8 and its protein coding genes in hepatocellular carcinoma

Abstract: Backgrounds: Hepatocellular carcinoma (HCC) is a lethal malignancy worldwide that is difficult to diagnose during the early stages and its tumors are recurrent. Long non-coding RNAs (lncRNAs) have increasingly been associated with tumor biomarkers for diagnosis and prognosis. This study attempts to explore the potential clinical significance of lncRNA DUXAP8 and its co-expression related protein coding genes (PCGs) for HCC. Method: Data from a total of 370 HCC patients from The Cancer Genome Atlas were utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…expression is markedly upregulated in HCC tumor tissues compared to that in corresponding normal tissues (Yue et al, 2019;Hu et al, 2020;Wang et al, 2020;Wei et al, 2020;Zhang et al, 2020). Jiang et al (2019) and Wang et al (2020) found that higher DUXAP8 expression is strongly associated with poor prognosis in HCC (Wang et al, 2020).…”
Section: Hepatocellular Carcinomamentioning
confidence: 97%
See 3 more Smart Citations
“…expression is markedly upregulated in HCC tumor tissues compared to that in corresponding normal tissues (Yue et al, 2019;Hu et al, 2020;Wang et al, 2020;Wei et al, 2020;Zhang et al, 2020). Jiang et al (2019) and Wang et al (2020) found that higher DUXAP8 expression is strongly associated with poor prognosis in HCC (Wang et al, 2020).…”
Section: Hepatocellular Carcinomamentioning
confidence: 97%
“…Emerging evidence suggests that lncRNAs are widely expressed and might function as promising therapeutic targets and prognostic indicators of various diseases and cancers ( Hu et al, 2019 ; Statello et al, 2021 ). DUXAP8 expression is markedly upregulated in HCC tumor tissues compared to that in corresponding normal tissues ( Yue et al, 2019 ; Hu et al, 2020 ; Wang et al, 2020 ; Wei et al, 2020 ; Zhang et al, 2020 ). Jiang et al (2019) and Wang et al (2020) found that higher DUXAP8 expression is strongly associated with poor prognosis in HCC ( Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Notably, there are other DUXAPs which are reported to be involved in tumor progression, such as lncRNA DUXAP10 acts as a diagnostic and prognostic marker for HCC, and promote HCC cell proliferation; 21,22 LncRNA DUXAP8, another DUXAP, also has been shown to serve as a pan‐cancer prognostic marker involved in molecular mechanisms contributing to HCC progression, 23,24 and DUXAP8 promotes HCC cell proliferation and migration by sponging miR‐490‐5p to induce BUB1 expression 25 . Importantly, a recent study has shown that lncRNA DUXAP10 promotes glioma cell stemness through enhancing sox12 mRNA stability 26 .…”
Section: Discussionmentioning
confidence: 99%